An economic analysis of the role of materials, system engineering, and performance in electrochemical carbon dioxide conversion to formate. (1st June 2022) - Badgett, Alex; Ruth, Mark; Crow, Allison; Grim, Gary; Chen, Yingying; Hu, Leiming; Tao, Ling; Smith, Wilson; Neyerlin, K.C.; Cortright, Randy
Abstract: The development of technologies that utilize carbon dioxide is important to mitigating climate change. The electrochemical reduction of carbon dioxide is one technology that can utilize greenhouse gasses that would be otherwise be emitted to the atmosphere by producing chemicals and fuels from carbon dioxide and electricity. Significant progress has been made in the experimental performance of carbon dioxide reduction systems with novel catalyst designs, new materials, and systems engineering; however, no work has linked such changes in stack design and materials to capital costs for the stack itself. Here we present an analysis that accounts for and analyzes the impacts of alternative materials and system architectures on manufactured costs of carbon dioxide reduction stacks, thus providing a framework to understand exactly how these advances impact the at-scale capital costs of these systems. Specifically, we consider the impact that the addition of a catholyte buffer layer has on an electrolyzer reducing carbon dioxide to formate, finding that the cost of manufacturing this part only increases stack costs by about $30/m 2 at high manufacturing rates, while previous work finds that this part improves system performance. This work shows that the links between system performance, materials, and costs are nonlinear, and that achieving low-cost scalability requires optimization of not just performance parameters but also the use of low-cost and highly scalable materials. These results bridge experimental and techno-economic analysis of processes for carbon dioxide reduction, informing researchers by providing a quantifiable estimate of the impact of advances in electrochemical carbon dioxide reduction technology on manufactured stack capital costs. Highlights: Estimates of manufactured cost of carbon dioxide reduction stacks are presented. Costs of two carbon dioxide reduction stack architectures are discussed. Case study estimating the economic impact of recent experimental advances is given. Cost optimization requires consideration of materials, performance, and scalability.